Brotherhood concept, Islamic accountability concept and Agency theory in relation to disclosure of annual report of zakat institutions: A proposed framework - Sapingi, Raedah; Puat Nelson, Sherliza; Sheikh Obid, Siti Normala (Pusat Pengajian Ekonomi, Fakulti Ekonomi Dan Pengurusan, Universiti Kebangsaan Malaysia, 2017)
Currently, theories and empirical works in disclosure study are clouded by the conventional perspective. Even though, there are efforts in discussing disclosure study based on Islamic view, nevertheless, it is still considered at the early stage. With regard to zakat institutions disclosure via annual report, the issue of accountability and information asymmetry have been raised in many past literatures. Realising the loopholes in theories of zakat institutions disclosure, thus, the study aims to propose a framework, by examining the two Islamic concepts i.e. brotherhood and Islamic accountability concept as well as conventional i.e. the agency theory, that would able to explain zakat institutions disclosure practices. Brotherhood concept introduces the idea of social justice, where zakat is seen as an antidote in ensuring the social-economic justice (al-adl) is attained, it promotes harmonious relationships with fellow human beings i.e. habl min al-nās, therefore in this context, the role of zakat institutions is to report their zakat activities via disclosure of zakat information in the annual report. While, accountability concept from Islamic perspective brings out the idea of primary and secondary accountability, zakat institutions are accountable to discharge their accountability to the users in relation to disclosure of zakat information. From conventional view, the agency theory describes agent- principal relationship. This section highlights interesting discussions, especially in providing justifications of using agency theory in this context. Finally, the application of the Islamic concepts and agency theory is then translated into a proposed framework.